Addressing controversies in the xylem embolism resistance–vessel diameter relationship. Issue 1 (3rd February 2023) - Isasa, Emilie; Link, Roman Mathias; Jansen, Steven; Tezeh, Fon Robinson; Kaack, Lucian; Sarmento Cabral, Juliano; Schuldt, Bernhard
Summary: Although xylem embolism is a key process during drought‐induced tree mortality, its relationship to wood anatomy remains debated. While the functional link between bordered pits and embolism resistance is known, there is no direct, mechanistic explanation for the traditional assumption that wider vessels are more vulnerable than narrow ones. We used data from 20 temperate broad‐leaved tree species to study the inter‐ and intraspecific relationship of water potential at 50% loss of conductivity ( P 50 ) with hydraulically weighted vessel diameter ( D h ) and tested its link to pit membrane thickness ( T PM ) and specific conductivity ( K s ) on species level. Embolism‐resistant species had thick pit membranes and narrow vessels. While D h was weakly associated with T PM, the P 50 – D h relationship remained highly significant after accounting for T PM . The interspecific pattern between P 50 and D h was mirrored by a link between P 50 and K s, but there was no evidence for an intraspecific relationship. Our results provide robust evidence for an interspecific P 50 – D h relationship across our species. As a potential cause for the inconsistencies in published P 50 – D h relationships, our analysis suggests differences in the range of trait values covered, and the level of data aggregation (species, tree or sample level) studied.